Improvement of Color Vision Following Posterior Cranial Vault Distraction for Crouzon Syndrome. Issue 4 (June 2018) - Asaad, Malke; Goyal, Samita; Klement, Kristen A.; Denny, Arlen D.
Abstract : Abstract: Crouzon syndrome (CS) is one of the craniosynostosis syndromes that leads to early fusion of cranial sutures and increased intracranial pressure. Intracranial hypertension is a serious complication that may lead to vision loss and cognitive impairment. Early detection and management are necessary to prevent complications. The authors present a patient with CS who underwent posterior cranial vault reconstruction with internal distraction after multiple episodes of headache and papilledema. The patient was unaware of any loss of color vision before the surgery; however, he noted an improvement in his color vision after the surgery. Color vision deficits may be an early sign of intracranial hypertension and finding these deficits using noninvasive testing methods may be an indication for early intervention.